Geographical analysis of seasonal relative humidity in northwestern Libya,For period (1968 - 2010) (Journal of Libya for geographical studies, 2024)
This study dealt geographical analysis with included five meteorological stations different in locations, topography, and climatic characteristics, these stations are Zwara on the Mediterranean sea coast, Tripoli Airport close to the sea, Gharyan and Nalut in the western mountain, and Ghadames station in the Libyan desert. The study relies on a dataset series 43 years, order to know the variation in the seasonal distribution of relative humidity in study area. The Ravenstein classification was used to determine relative humidity categories in the region, noted that there was fluctuation in the categories from station to another and from season to season. The Pearson correlation coefficient was applied to find the statistical relationship between the seasonal averages of relative humidity and temperatures as an independent factor with a direct influence on the humidity component, the results showed a weak inverse relationship in most seasons of the year, especially spring, summer and annual average in Ghadames station, with some relationships positive weak and medium as in the spring in Gharyan station and in winter in Nalut station.
Keywords: Geographical analysis; relative humidity; Ravenstein; limate change; NW Libya